An augmented teachable agent for elderly - Silver Agent - Tao, Ping (2016)
Teachable agent is a special type of pedagogical agent which applies Learning-by-Teaching theory through simulating a naive learner in order to motivate students to teach it and in return improve their learning capacity. This paper proposes an augmented teachable agent, the Silver Agent, for the elderly most of whom experience a loss of cognitive skills. The Silver Agent aims to help them to rebuild their cognitive skills through integrating with a cognitive game, the Empathy Map, to simulate cognitive trainings. More importantly, the Silver Agent inherits the main function of relational agents which is to establish long-term relationships with the users, thus serving as a learning companion for them. An experiment, which involves 8 elderlies who aged 65 or over, was conducted to evaluate the performance of the agent in terms of the quality of the relationship built and user’s cognitive learning outcome with both focus group study and quantitative analysis approaches. The results show that most of the participants felt the sense of accompanying and learning outcomes has also shown a tendency to improve, both of which indicate the results are aligned with the agent’s objectives.